Novel potent and selective pyrazolylpyrimidine-based SYK inhibitors. Issue 22 (15th November 2020) - Barlaam, Bernard; Boiko, Scott; Boyd, Scott; Dry, Hannah; Gingipalli, Lakshmaiah; Ikeda, Timothy; Johnson, Tony; Kawatkar, Sameer; Lorthioir, Olivier; Pike, Andy; Pollard, Hannah; Read, Jon; et al.
Graphical abstract: Abstract: Hybridisation of amino-pyrimidine based SYK inhibitors (e.g. 1a ) with previously reported diamine-based SYK inhibitors (e.g. TAK-659) led to the identification and optimisation of a novel pyrimidine-based series of potent and selective SYK inhibitors, where the original aminomethylene group was replaced by a 3, 4-diaminotetrahydropyran group. The initial compound 5 achieved excellent SYK potency. However, it suffered from poor permeability and modest kinase selectivity. Further modifications of the 3, 4-diaminotetrahydropyran group were identified and the interactions of those groups with Asp512 were characterised by protein X-ray crystallography. Further optimisation of this series saw mixed results where permeability and kinase selectivity were increased and oral bioavailability was achieved in the series, but at the expense of potent hERG inhibition.